VARIASI BIOBRIKET CANGKANG PALA TERHADAP KARAKTERISTIK TERMAL SEBAGAI SUMBER BELAJAR MATERI KALOR - Rahmad fakhrullah; Fera Annisa; Nur Aida; Fitriyawany; Muhammad Nasir (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2024)
This research explores the potential of nutmeg shells as an alternative energy source in the form of biobriquettes and their use as a learning resource for understanding heat materials. This research was also motivated by the lack of utilization of nutmeg shells, which are rich in energy. The aim of this research is to determine the process of making charcoal biobriquettes from nutmeg shell waste, determine the characteristics of the biobriquettes produced, and determine students' responses to the biobriquettes that have been developed. This research method uses an experimental approach, with a focus on the physical and chemical characteristics of biobriquettes. The results of research on the process of making charcoal biobriquettes from nutmeg shell waste go through several stages, namely drying, burning, grinding, mixing with adhesive and water, molding, and drying in the sun. The revealing variations in the characteristics of nutmeg shell biobriquettes at carbonization temperatures of 400°C, 450°C, and 500°C, including density, water content, ash content, and heating value. The percentage of students' responses to biobriquettes in heat learning was 76.25%. Thus, it can be concluded that the process of making charcoal briquettes from nutmeg shell waste can be produced as an alternative energy that meets the characteristics of biobriquettes in accordance with the Indonesian National Standards, and also students' responses to the biobriquettes that were developed are very suitable as a source of learning heat material.